2021
DOI: 10.1002/cjoc.202100709
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Decarboxylative/Defluorinative Alkylation for the Synthesis of gem‐Difluoroalkenes through an SN2’‐Type Route

Abstract: Comprehensive Summary An efficient decarboxylative/defluorinative alkylation for synthesizing gem‐difluoroalkenes is described, providing a general method for installation of the challenging alkyl fragments containing α‐electron‐withdrawing groups into α‐trifluoromethyl alkenes. Mechanistic studies suggest that this process involves an SN2′‐type synthetic route in the absence of transition‐metal catalysts or photocatalysis. Moreover, this protocol can easily be scaled up, and successfully applied to the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…On the basis of the experimental results aforementioned and the previous reports, 4–17 we proposed a radical-type mechanism for this Fe-catalysed defluorinative cross-coupling reaction (Scheme 6). At the beginning, Fe + complex I is formed under reductive reaction conditions, 14 followed by single-electron-transfer with the bromodifluoroacetate 2a .…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…On the basis of the experimental results aforementioned and the previous reports, 4–17 we proposed a radical-type mechanism for this Fe-catalysed defluorinative cross-coupling reaction (Scheme 6). At the beginning, Fe + complex I is formed under reductive reaction conditions, 14 followed by single-electron-transfer with the bromodifluoroacetate 2a .…”
mentioning
confidence: 73%
“…3 Due to the high reactivity of trifluoromethyl olefins, a series of reactions can occur with other reagents under the action of metal catalysts, so the study of such reactions has also attracted the interest of many research groups. 4–8 Wang, 4 Fu, 5 Cao, 6 Feng 7 and other related research groups 8 reported a series of Ni-catalyzed related coupling reactions of trifluoromethyl olefins to synthesize the corresponding gem -difluoroolefins.…”
mentioning
confidence: 99%
“…It is well known that alkyl carboxylic acids could undergo radical decarboxylation via single electron oxidation to generate alkyl radicals [12][13][14] . When treated with base, the nucleophilic C(sp 3 ) intermediates can be generated by ionic decarboxylation [15][16][17][18][19][20] . Based on the previous work, a plausible mechanistic pathway is proposed in Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the groups of Molander, 7 Wang, 8 and others 9 have demonstrated some elegant examples based on catalysing the cleavage of carbon-heteroatom bonds (such as carbon-halogen/-boron/-silicon/-oxygen bonds) in the presence of transition-metal catalysts or photocatalysts (Scheme 1a). Alternatively, the synthesis of gem -difluoroalkenes by catalytic carbon–carbon bond cleavage (Scheme 1b, left), especially using carboxylic acids and their derivatives as convenient radical precursors, has also been well developed by the groups of Zhou, 10 Fu 11 and others. 12 However, despite these advances in thermal and photochemical defluorinated alkylation methods, the development of novel radical precursors for gem -difluoroalkene synthesis is still in great demand, especially those enabled by metal-free catalysis.…”
Section: Introductionmentioning
confidence: 99%